Implementasi Media Pembelajaran Wordwall Dalam Meningkatkan Motivasi Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Di SD Islam Al Muttaqin Sawahlunto - Melvi; Kustati, Martin; Amelia, Rezki; Gusmirawati (STAI Tebing Tinggi Deli, 2024)
This study aims to analyze the implementation of Wordwall-based learning media to increase student motivation in the Islamic Religious Education (PAI) subject at SD Islam Al Muttaqin, Sawahlunto. Wordwall, as an interactive learning medium, offers various forms of quizzes, games, and engaging learning activities easily accessible to students, which are expected to enhance their interest and enthusiasm for learning. The research method used is classroom action research (CAR) with a qualitative approach. Data collection was conducted through observation, interviews, and questionnaires, involving PAI teachers and students as research subjects. The data obtained were analyzed using qualitative descriptive analysis techniques to understand the impact of implementing Wordwall media on students' learning motivation. The study results indicate that using Wordwall significantly increased students' learning motivation. Students appeared more enthusiastic and actively engaged in learning and showed improved comprehension of PAI material. Wordwall's use also facilitated teachers in delivering material in a varied and interactive way, creating a fun and effective learning environment. These findings suggest that Wordwall can be an innovative solution in PAI learning at the elementary school level, especially in attracting students' interest in learning. In conclusion, implementing Wordwall as a learning medium can increase students' motivation to learn and positively impact Islamic Religious Education learning at SD Islam Al Muttaqin, Sawahlunto.